The Mediation Role Of Job Satisfaction On Turnover Intention at Outsourcing Security PT X. - Ainur Eka Fauzia; Hesty Prima Rini (JURNAL MANAJEMEN MOTIVASI, 2026)
The purpose of this study is to evaluate the relationship between compensation and job demands on the intention to leave the job, along with job satisfaction as a mediating variable in PT X. This study uses a quantitative approach using SEM-PLS analysis techniques. The results show that compensation has a significant negative impact on the intention to leave the job. Job demand increases turnover intention. Job satisfaction has been shown to mediate the effect of compensation and job demands on the intention to leave the job. The results show the importance of job satisfaction as a psychological mechanism that connects employee behavior with organizational elements. This study helps expand research on turnover intention in the context of security outsourcing which is still limited.